Global marketing and globalization miths Os mitos do marketing global e da globalização - Renato Rodrigues Martins (Discursos Fotográficos, 2012)
Global marketing and advertising: understanding cultural paradoxes, de Marieke de Mooij, 3rd ed. Thousand Oaks, CA. Sage Publications, 2010, 322p. Global marketing and advertising: understanding cultural paradoxes, de Marieke de Mooij, 3rd ed. Thousand Oaks, CA. Sage Publications, 2010, 322p.